Variations in the properties and bacterial community of white glutinous rice tapai under different packaging conditions during fermentation - TATI BARUS; NOVIANA CENNIATI; VIVITRI DEWI PRASASTY (Society for Indonesian Biodiversity, 2023)
Abstract. Barus T, Cenniati N, Prasasty VD. 2023. Variations in the properties and bacterial community of white glutinous rice tapai under different packaging conditions during fermentation. Biodiversitas 24: 6240-6247. White Glutinous Rice Tapai (WGRT) is a traditional Indonesian fermented food. Several types of packaging can be used for white glutinous rice tapai (WGRT). However, information about the effects of different types of packaging on characteristics and bacterial communities has not yet been discovered. Therefore, this study aimed to evaluate the effect of packaging on the quality of WGRT. WGRT was fermented using a plastic box (WGRT-PB), banana leaves (WGRT-BL), and rose apple leaves (WGRT-RAL). Our research employed a novel method using next-generation sequencing (NGS), to explore the bacterial communities in the fermentation process of white glutinous rice tapai, offering valuable insights into how the choice of packaging materials affects the organoleptic properties of the final product. The results showed that the type of packaging did not significantly affect pH, total acid, and alcohol content but significantly reduced sugar content. The highest levels of reducing sugar were found in WGRT-PB. The organoleptic profile showed that WGRT-PB was the most preferred by the panelists, significantly different from WGRT-RAL. The results of the bacterial community analysis between WGRT-PB and WGRT-RAL showed a difference. The difference in the bacterial community was presumably due to the different types of packaging used during fermentation. Thus, the different types of packaging used during fermentation affect the quality of the tapai.